The market power of OPEC 1973-2001 - Petter Vegard Hansen; Lars Lindholt (Statistics Norway, Research Department, 2004)
We apply a multi-equation dynamic econometric model on monthly data to test if the behaviour of OPEC as a whole or different sub-groups of the cartel is consistent with the characteristics of dominant producers on the world crude oil market in the period 1973-2001. Our results indicate that the producers outside OPEC can be described as competitive producers, taking the oil price as given and maximising profits. The OPEC members do not fit the behaviour of price-taking producers. Our findings of low residual demand price elasticities for OPEC underpin the potential market power of the producer group, and are in line with the results in some recent energy studies. On the other hand, our findings indicate that neither OPEC nor different sub-groups of the cartel can be characterised as a dominant producer in the period 1973-1994. However, we find that the characteristics of a dominant producer to some extent fit OPEC-Core as from 1994. Thus, although OPEC clearly has affected the market price, the producer group has not behaved as a pure profitmaximising dominant producer.
Keywords: C32; L13; L71; Q30; 330; Oil market; OPEC; Market power; Equilibrium Correction Mechanism model